1005. DROSERA ALLANTOSTIGMA: Droseraceae. (11th October 2021) - Cross, Adam T.; Krueger, Thilo A.
Summary: Drosera allantostigma (N.G.Marchant & Lowrie) Lowrie & Conran is illustrated and described. The species is a tiny herbaceous carnivorous plant native to a single roadside location in Western Australia, from which it has not been observed in almost a decade. Weed encroachment, agricultural runoff and altered hydrology continue to affect the location. We discuss the conservation status and threats facing the species, and suggest that D. allantostigma may be the first Australian carnivorous plant to have become extinct in the wild.